Nomograms predicting long-term overall survival and cancer-specific survival in head and neck squamous cell carcinoma patients - Ju, Jun (Oncotarget, 2016)
This study aimed to develop nomograms to predict long-term overall survival and cancer-specific survival in patients with head and neck squamous cell carcinoma (HNSCC). We conducted prognostic analyses and developed nomograms predicting survival outcome using HNSCC patient data collected from the Surveillance, Epidemiology and End Results (SEER) program of the National Cancer Institute. An external dataset of 219 patients was used to validate the nomograms. Of 36,179 HNSCC patients, 9,627 (26.6%) died from HNSCC and 4,229 (11.7%) died from other causes. Median follow-up was 28 months (1-107 months). Nomograms predicting overall survival (OS) and cancer-specific survival (CSS) were developed according to 10 clinicopathologic factors (age, race, sex, tumor site, tumor grade, surgery, radiotherapy and TNM stage), with concordance indexes (C-indexes) of 0.719 and 0.741, respectively. External validation C-indexes were 0.709 and 0.706 for OS and CSS, respectively. Our results suggest that we successfully developed nomograms predicting five- and eight-year HNSCC patient OS and CSS with high accuracy. These nomograms could help clinicians tailor surgical, adjuvant therapeutic and follow-up strategies to more effectively treat HNSCC patients.